A SULAPA EPPE’E MODEL CONSTRUCTION FOR THE LEGAL PROTECTION OF THE LIFE ENVIRONMENT IN THE COASTAL FISHING RESOURCE EXPLOITATION AT SOUTH SULAWESI PROVINCE - Ilyas , Ilyas; Kusuma , Apriliani (IJBLE Scientific Publications Community Inc., 2023)
This research analyzes the construction model of Sulapa Eppe'e in environmental law protection for the utilization of coastal fishery resources. This type of research uses a normative-empirical constructivism paradigm. The results of the study show that Sulapa Eppe'e adheres to a four-dimensional system of legal relations that places humans as the center in relations with God, nature (environment), society, and the government and the state. Model construction includes: concepts, philosophies, paradigms, ideologies, basic values, norms, principles, analytical methods and practices. This model gave birth to three pillars of wisdom, namely local wisdom, ecological wisdom, and the legal wisdom of the Mampanre'tasi tradition (conservation and zoning system), Rompong (protection and management system), Pemali and Palili'(prevention and repressive system), Mamia Kadialo (ecological wisdom values), Ponggawa – sawi (coordination and cooperation system). The Sulapa Eppe'e model can play an important role in overcoming tensions, integrating and harmonizing political products, ecological products and cultural products from environmental law.